2021
DOI: 10.14348/molcells.2021.2229
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin D Promotes Progression of Oral Squamous Cell Carcinoma via NF-Kappa B Signaling

Abstract: Ubiquitin D (UBD) is highly upregulated in many cancers, and plays a pivotal role in the pathophysiological processes of cancers. However, its roles and underlying mechanisms in oral squamous cell carcinoma (OSCC) are still unclear. In the present study, we investigated the role of UBD in patients with OSCC. Quantitative real-time polymerase chain reaction and Western blot were used to measure the expression of UBD in OSCC tissues. Immunohistochemistry assay was used to detect the differential expressions of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Ubiquitin-fold modifier 1 (UFM1) is a newly discovered ubiquitin-like protein ( Komatsu et al, 2004 ). Like ubiquitin and other ubiquitin-like proteins ( Song et al, 2021 ), UFM1 is conjugated to target proteins by a three-step enzyme system: UBA5, a UFM1-activating E1 enzyme; UFC1, a UFM1-conjugating E2 enzymes; and UFL1, a UFM1 E3 ligases ( Daniel and Liebau, 2014 ; Komatsu et al, 2004 ; Yoo et al, 2015 ). In addition, a UFM1-binding protein (UFBP1, also known as DDRGK1) is required for protein modification by UFM1 ( Yoo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin-fold modifier 1 (UFM1) is a newly discovered ubiquitin-like protein ( Komatsu et al, 2004 ). Like ubiquitin and other ubiquitin-like proteins ( Song et al, 2021 ), UFM1 is conjugated to target proteins by a three-step enzyme system: UBA5, a UFM1-activating E1 enzyme; UFC1, a UFM1-conjugating E2 enzymes; and UFL1, a UFM1 E3 ligases ( Daniel and Liebau, 2014 ; Komatsu et al, 2004 ; Yoo et al, 2015 ). In addition, a UFM1-binding protein (UFBP1, also known as DDRGK1) is required for protein modification by UFM1 ( Yoo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram could help to screen for high-risk patients and determine more aggressive treatment regimens for high-risk patients with glioma (31,32). Although few study show that UBD expression could be a prognostic factor for glioma, a large number of relevant studies have revealed that UBD expression could be an adverse prognostic biomarker for various tumors (11,13,33,34). These results suggest that UBD has the potential to become a diagnostic marker in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…UBD modulates various signaling pathways involved in tumor development, such as NF-κB and Wnt/β-catenin signaling pathways ( 16 , 50 ). Notably, UBD accelerates the progression of oral squamous cell carcinoma via NF-κB signaling ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…UBD modulates various signaling pathways involved in tumor development, such as NF-κB and Wnt/β-catenin signaling pathways ( 16 , 50 ). Notably, UBD accelerates the progression of oral squamous cell carcinoma via NF-κB signaling ( 50 ). Elevated UBD expression has been shown to drive the invasion and metastasis of hepatocellular carcinoma cells by binding to β-catenin to prevent its ubiquitylation and degradation ( 51 ).…”
Section: Discussionmentioning
confidence: 99%